A Report on Extent, Forms and Linkages of Common Property Land in Kosi Embankment Area, North Bihar - Planning Commission (Planning Commission, 1988)
The preamble to Constitution of India, adopted in 1950 mentions that social, economic and political justice would be secured for all the people so that among other things the people are secured the adequate means of their livelihood. Planners in India addressed themselves to the problem of ensuring the minimum requirements of the poor under the leadership of late Pitambar Pant in 1962 and since then providing the minimum needs of the poor have become an integral of the five year planning in India.
Planning Commission Government of India
Planning Commission Government of India